2022
DOI: 10.1021/accountsmr.2c00072
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Nano–Bio Interfaces from Nanomaterials to Nanomedicines

Abstract: The nano−bio interface refers to the physical interface between the biological system and nanoscale surface topography, functioning as the barrier between two phases where critical reactions occur. In the last two decades, advances in nanofabrication techniques have heralded a new research area utilizing precisely engineered surfaces and structures to control cell cycles, pathways of metabolism, immune responses, and so forth. At the cellular level, engineered nanomaterials (ENMs) with typical surfaces and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 60 publications
0
27
0
1
Order By: Relevance
“…Biocompatibility of DCT/ bi GC@PNA + RF was evaluated through serum biochemistry and hematological assessments. , DCT (80 μmol L –1 , 100 μL, i.v .) and bi GC@PNA (21.22 mmol L –1 of Au content, 100 μL, i.t .)…”
Section: Methodsmentioning
confidence: 99%
“…Biocompatibility of DCT/ bi GC@PNA + RF was evaluated through serum biochemistry and hematological assessments. , DCT (80 μmol L –1 , 100 μL, i.v .) and bi GC@PNA (21.22 mmol L –1 of Au content, 100 μL, i.t .)…”
Section: Methodsmentioning
confidence: 99%
“…82 Patients with high levels of anti-PEG antibodies could have a severe allergic reaction, and the immunogenicity could be reduced by the regulation of nano-protein corona. 83,84 Secondly, local injection pain and systemic or local inflammatory reactions (malaise, fever) are the most common adverse events. 85 In the phase 3 studies of BNT162b2 and mRNA-1273, more than 80% of LNP-mRNA recipients reported local adverse events and mainly pain.…”
Section: Prepared a Series Of Lnps With Differentmentioning
confidence: 99%
“…The properties that make ENMs technologically interesting—nanoscale size and high reactivity, among other unique characteristics—are the same that raise flags concerning their potential adverse effects on human health and the environment. The interactions of nanoparticles with biological systems are detrimental to the safety and efficacy of nanomaterials/nanomedicines [ 12 ]. Therefore, the limited understanding of the nano–bio interactions may hamper the use and commercialization of ENMs, impacting the development of the whole field of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%